Retention dependences support highly confident identification of lipid species in human plasma by reversed-phase UHPLC/MS - Vaňková, Zuzana; Peterka, Ondřej; Chocholoušková, Michaela; Wolrab, Denise; Jirásko, Robert; Holčapek, Michal (Analytical and bioanalytical chemistry, 2022)
Reversed-phase ultrahigh-performance liquid chromatography-mass spectrometry (RP-UHPLC/MS) method was developed with the aim to unambiguously identify a large number of lipid species from multiple lipid classes in human plasma. The optimized RP-UHPLC/MS method employed the C18 column with sub-2-μm particles with the total run time of 25 min. The chromatographic resolution was investigated with 42 standards from 18 lipid classes. The UHPLC system was coupled to high-resolution quadrupole-time-of-flight (QTOF) mass analyzer using electrospray ionization (ESI) measuring full-scan and tandem mass spectra (MS/MS) in positive- and negative-ion modes with high mass accuracy. Our identification approach was based on m/z values measured with mass accuracy within 5 ppm tolerance in the full-scan mode, characteristic fragment ions in MS/MS, and regularity in chromatographic retention dependences for individual lipid species, which provides the highest level of confidence for reported identifications of lipid species including regioisomeric and other isobaric forms. The graphs of dependences of retention times on the carbon number or on the number of double bond(s) in fatty acyl chains were constructed to support the identification of lipid species in homologous lipid series. Our list of identified lipid species is also compared with previous publications investigating human blood samples by various MS-based approaches. In total, we have reported more than 500 lipid species representing 26 polar and nonpolar lipid classes detected in NIST Standard reference material 1950 human plasma.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Lipidomics; lipidy; Reversed-phase; lidé; Mass spectrometry; Human plasma; Chromatography, Liquid; Retention behavior; chromatografie kapalinová; Lipids; Ultrahigh-performance liquid chromatography; Humans